SÍNTESE DOS ESTUDOS ICNOLÓGICOS DO GRUPO ITARARÉ NO RIO GRANDE DO SUL - DIAS-FABRÍCIO, MARIA ELICE; GUERRA-SOMMER, MARGOT (Pesquisas em Geociências, 1989)
Several ichnocoenosis from varved shales of the Itararé Group, Rio Grande do Sul State, previously describe by GUERRA-SOMMER et all (1984), GUERRA-SOMMER et all (1985) and DIAS-FABRÍCIO et all (1985) are registred. The association consist mainly of traces of locomotion (Repichnia), occurring also grazing traces (Pascichnia) and resting traces (Cubichnia). The ichnological analyses gave important support for interpretation of the depositional environment associated with lacustrine sedimentation with glacial influence.